MEASURING USABILITY AND USER EXPERIENCE IN EARLY IMPLEMENTATION OF WESIHAT3.0 - Dwi Fiqri Qurniawan; Nazlena Mohamad Ali; Mohamad Hidir Mhd Salim; Shaharizal Othman (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Mobile applications are designed and developed to cater for various use by their targeted user. The recent rapid evolution of software development technology has enabled the implementation of various forms of interactive mobile applications for users of all ages of life. The technology employed in the development process can impact users, particularly regarding the mobile applications appearance, functionalities, usability and acceptance by the intended user. This research investigates the level of usability and user experience of an initial design for a mobile application named WESIHAT 3.0 using the System Usability Scale (SUS) instrument. WESIHAT 3.0 is a mobile educational application designed and developed to improve the cognitive ability of older adults. To make WESIHAT3.0 acceptable to the intended user, it is paramount that the usability and user experience must reach an acceptable level. This study’s findings will be utilized to improve the usability and user experience of WESIHAT3.0 and make it more acceptable to the target audience.